2012
DOI: 10.1148/radiol.12110224
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging of Pulmonary Embolism: Diagnostic Accuracy of Contrast-enhanced 3D MR Pulmonary Angiography, Contrast-enhanced Low–Flip Angle 3D GRE, and Nonenhanced Free-Induction FISP Sequences

Abstract: There are complementary benefits to combining standard MR pulmonary angiography, 3D GRE, and triggered true FISP MR examinations for evaluation of PE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
71
3
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 16 publications
(17 reference statements)
12
71
3
3
Order By: Relevance
“…Additionally, there is a growing awareness of potential risks associated with ionizing radiation and increased CT angiography use, especially in young patients (5). Contrast material-enhanced magnetic resonance (MR) angiography is emerging as an attractive nonionizing alternative with which to detect PE (4,(6)(7)(8)(9)(10)(11).…”
Section: Implications For Patient Carementioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, there is a growing awareness of potential risks associated with ionizing radiation and increased CT angiography use, especially in young patients (5). Contrast material-enhanced magnetic resonance (MR) angiography is emerging as an attractive nonionizing alternative with which to detect PE (4,(6)(7)(8)(9)(10)(11).…”
Section: Implications For Patient Carementioning
confidence: 99%
“…Previous studies have reported varying diagnostic performance with current MR angiography methods (4,(7)(8)(9)(10)(11). The recent multicenter PIOPED III study showed a sensitivity and specificity for acute PE of only 78% and 99%, respectively (4).…”
Section: Experimental Studies: Pulmonary Embolism Detection Bannas Et Almentioning
confidence: 99%
“…In recent studies, balanced SSFP, or called TrueFISP, has been used in cardiovascular imaging. TrueFISP has demonstrated high specificity for evaluation of pulmonary embolism (17). Compared to contrastenhanced MRA, high image quality, high SNR and CNR were found in imaging of different target vessels (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Recentemente, Kalb e cols. 58 avaliaram a detecção de TEP através da angiorressonância magnética pulmonar padrão com injeção de contraste e aquisição de imagens em apneia, através da técnica de recirculação de fase de contraste tridimensional gradiente-echo utilizando baixo flip angle e através da sequência de imagem sem realce true fast com steady-state precession. Eles acharam que as três sequências combinadas aumentaram a sensibilidade para 84%.…”
Section: Angiorressonância Magnética E Tepunclassified
“…Eles acharam que as três sequências combinadas aumentaram a sensibilidade para 84%. A especificidade foi de 100% para todos os métodos, exceto para a angiorressonância magnética pulmonar (1 falso-positivo) 58 .…”
Section: Angiorressonância Magnética E Tepunclassified